Visual Aesthetics of Batik Cloth in the Mitoni Ritual of Surakarta - Wahyuningrum, RA Heryani; Jasjfi, Elda Franzia (VCD: Journal of Visual Communication Design, 2025)
This research examines the visual aesthetics and symbolic meaning of batik cloth used in the Javanese Mitoni ritual in Surakarta, a traditional ceremony held during the seventh month of pregnancy to pray for the safety of the mother and child. The study employs a qualitative iconographic approach to analyze the form, motif, and symbolism of batik cloth selected for the ritual. Data were collected through direct observation and interviews with ritual practitioners and families who conducted the ceremony. The analysis reveals that each batik motif carries philosophical meanings representing prayers for protection, fertility, and harmony. The cloth used within the Surakarta Palace tradition demonstrates strong ties between visual art and spiritual belief, functioning as both aesthetic expression and cultural identity. The findings highlight the importance of preserving batik as part of Indonesia’s intangible heritage and its role as a visual language of hope and continuity in Javanese culture.